A case study of leak testing method for diffusion pump - Siti Nur Aida Abu Bakar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project is related to a real industry case involving the Quality Assurance Department for UWC Holdings Sdn. Bhd. In this project the problems and proposal of solution were presented to solve the problems that occurred in the leak testing for diffusion pump section. Due to leak test has various method, the proposal of solution that were discussed in this paper is by using Outsidein Helium Spraying Method.